Draft Annual Plan (1972-73) Part-I Union Territory of Delhi - Planning Commission (Planning Commission, 1971)
Planning in the Union Territory of Delhi has to take into account the following special features of—its development needs: a) In view of its predominant urban character, this Territory has peculiar development problems. b) The population of Delhi has been increasing at a phenomenal rate which is unparalleled in any city of the country.
Union Territory of Delhi Administration Planning Department